Association between Mediterranean diet and metabolic health status among adults was not mediated through serum adropin levels - Maryam Shafiei; Donya Poursalehi; Sobhan Mohammadi; Farnaz Shahdadian; Zahra Hajhashemy; Parisa Rouhani; Elahe Mokhtari; Parvane Saneei (BMC Public Health)
Abstract Background Prevalence of metabolic disorders has been increased in recent years around the world. The relationship between Mediterranean diet (MD) with metabolic health status and serum adropin levels has been less examined in Iranian adults. We investigated the association between MD compliance with metabolic health status and adropin hormone in Iranian adults. Methods This observational study was conducted on 527 men and women. Food intakes were evaluated by a validated food frequency questionnaire. Blood pressure and anthropometric parameters were measured. Fasting blood samples were drawn to measure serum adropin concentrations, blood glucose, triglycerides, high-density lipoprotein cholesterol, high sensitive C-reactive protein and insulin. Metabolic unhealthy (MU) status was defined as having ≥ 2 cardio-metabolic risk factors. Results After adjustments for potential confounders, subjects in highest versus lowest tertile of MD had 52% lower odds of MU status (OR = 0.48, 95%CI: 0.23–0.97). Stratified analysis revealed a significant association in normal-weight participants (OR = 0.12; 95%CI: 0.02–0.64), but not in those with overweight/obesity (OR = 0.66, 95%CI: 0.27–1.57). By excluding each component of MD, the association disappeared, except for three components (vegetables, nuts and grains). MD adherence was not significantly related to serum adropin levels in multivariable-adjusted model (unstandardized B= -0.19, 95%CI: -4.97, 4.59; P = 0.94). Serum adropin hormone levels were also not substantially different among metabolic healthy versus unhealthy subjects (P = 0.66). Conclusions This cross-sectional study showed an inverse association between adherence to MD and odds of MU status, especially in subjects with normal-weight. Serum adropin concentrations were not associated with MD adherence or metabolic health status.